Spatial Atomic Layer Deposition of Molybdenum Oxide for Industrial Solar Cells. Issue 22 (5th October 2020) - Gregory, Geoffrey; Luderer, Christoph; Ali, Haider; Sakthivel, Tamil S.; Jurca, Titel; Bivour, Martin; Seal, Sudipta; Davis, Kristopher O.
Abstract: Molybdenum oxide thin films are successfully deposited using spatial atomic layer deposition (SALD), a tool designed for high‐throughput industrial film growth. The structural and optical properties of the film are evaluated using ultraviolet photoelectron spectroscopy, high‐resolution transmission electron microscopy, and spectroscopic ellipsometry. To demonstrate the applicability of molybdenum oxide in industrial settings the films are applied as hole‐selective silicon heterojunction contacts for solar cells. When paired with intrinsic amorphous silicon passivation layers, implied open‐circuit voltages of 699 mV are achieved. The carrier transport is unaffected by low‐temperature contact anneals up to 300 °C with contact resistivities of ≈ 10 mΩ cm 2 . Finally, the optical performance of silicon solar cells featuring different front hole‐selective heterojunction structures are simulated. It is shown that the generation current density of heterojunction solar cells can be significantly increased with the addition of SALD molybdenum oxide contacts. Abstract : Molybdenum oxide thin films are successfully deposited using spatial atomic layer deposition (SALD), a tool designed for high‐throughput industrial film growth. The structural and optoelectronic properties of the film are evaluated for applications in silicon solar cell technologies. The results present a promising future for SALD in industrial settings such as photovoltaics manufacturing.